A Holography-Based Modal Wavefront Sensor for the Precise Positioning of a Light Emitter Using a High-Resolution Computer-Generated Hologram - Loosen, Florian; Stehr, Johannes; Alber, Lucas; Harder, Irina; Lindlein, Norbert (Ieee Photonics Journal, 2018)
In certain applications, modal wavefront sensors (MWFSs) can outperform zonal wavefront sensors, which are widely used due to their high ﬂexibility. In this paper, a holography-based MWFS as described is developed for the fast position control of a light emitter in a deep parabolic mirror. The light source is located in the vicinity of the focal point. Instead of Zernike polynomials, more complex phase functions, which are related to certain dislocations of the light source are used as detector modes. The performance of the sensor is veriﬁed with a test setup, where the test wavefront is generated by a spatial light modulator instead of a real parabolic mirror. The design and fabrication of the required high-resolution holographic element is described and an easy way of multiplexing several single mode sensors is demonstrated.
Keywords: advanced optics design; diffractive optics; holography

Design und Herstellung eines CGH-basierten Modalen Wellenfrontsensors - Stehr, Johannes; Loosen, Florian; Lindlein, Norbert; Alber, Lucas (118. DGaO-Jahrestagung, 2017)
Modale Wellenfrontsensoren können gegenüber einer zonalen Wellenfrontdetektion von Vorteil sein. Etwa, wenn in einem optischen Element fabrikationsbedingt nur spezielle Aberrationsmoden zu erwarten sind. Der Hauptvorteil eines modalen Sensors ist die geringe Auswertekomplexität und folglich ein Geschwindigkeitsvorteil bei der Wellenfrontmessung. Als modale Basis können die Zernike-Polynome dienen, deren Koeffizienten durch Messung der Phasenfront bestimmt werden können. Sind die zu erwartenden Aberrationen für ein optisches Element bekannt, kann die Funktionsweise diesbezüglich optimiert werden. Unser Ziel ist es, einen Wellenfrontsensor auf Basis eines Computer-Generierten Hologramms zu realisieren (Neil et al. 2000). Das Prinzip des Sensors basiert auf der holografischen Rekonstruktion einer ebenen Objektwelle durch eine spezifisch aberrierte Referenzwellenfront. Wir werden die quantitative Untersuchung des intermodalen Crosstalks eines modalen Wellenfrontsensors präsentieren, welcher zur genauen Messung von Defokus und Koma ausgelegt ist. Die Charakterisierung des intermodalen Crosstalks ist dabei notwendig, um ein möglichst effizientes und genaues Sensorverhalten zu erzielen.

Focusing characteristics of a 4pi parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (arXiv, 2016)

Focusing characteristics of a 4π parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2017)

Measuring the temperature and heating rate of a single ion by imaging - Srivathsan, Bharath; Fischer, Martin; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2019)

Shifting the phase of a coherent beam with a 174Yb+ ion: influence of the scattering cross section - Fischer, Martin; Srivathsan, Bharath; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2017)
We discuss and measure the phase shift imposed onto a radially polarized light beam when focusing it onto an Yb ion. In the derivation of the expected phase shifts, we include the properties of the involved atomic levels. Furthermore, we emphasize the importance of the scattering cross section and its relation to the efficiency for coupling the focused light to an atom. The phase shifts found in the experiment are compatible with the expected ones when accounting for known deficiencies of the focusing optics and the motion of the trapped ion at the Doppler limit of laser cooling (Hänsch and Schawlow in Opt Commun 13:68–69, 1975).